TEMPORARY RESIDENTIAL DESIGN ANALYSIS TYPE OF HEX HOUSE FOR DISASTER SURVIVAL IN INDONESIA - Awaluddin Azril; Mirza Irwansyah; Yunita Idris (RADJA PUBLIKA, 2022)
Temporary shelter (huntara) is an effort to fulfill basic human needs for survivors after a disaster. Shelters aim to provide protection with dignity, a sense of security and comfort, fulfillment of social needs, and easy access to finding a livelihood. The research object refers to the Hex House Type shelter design. This study aims to determine the feasibility standard indicators that are met by the design. Design feasibility indicators are measured through the “six key eligibility criteria” approach based on the concept formulation of Jo Da Silva and C.Crook. The research method uses a qualitative approach with descriptive analysis. Data sourced from document review. The results obtained, the Hex House design in general meets the indicators to be implemented in Indonesia.